CANCER HUBUNGAN ANTARA -RELATED FATIGUE DENGAN KUALITAS HIDUP PADA PASIEN KANKER PALIATIF DI IRNA 1 RSUP DR. SARDJITO YOGYAKARTA - , RIZKY INDRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Palliative cancer cannot be cured, it is known as end stage or terminal cancer. Palliative cancer patients generally encounter fatigue called cancer-related fatigue (CRF), i.e. intense, chronic and distracting symptom that cannot be resolved by rest. CRF affects ability of the patient in doing daily activities, working, fulfilling needs and maintaining independence. In the long run it can affect quality of life. Objective: The study aimed to identify correlation between CRF and quality of life of palliative cancer patients at IRNA 1 RSUP Dr. Sardjito Yogyakarta. Method: The study used quantitative non experimental with analitic and cross sectional design. As many as 30 respondents (n=30) got questionnaire of Visual Analogue Scale for Fatigue (VAS-F) to assess CRF and questionnaire of quality of life named European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) Indonesian version. Analysis used bivariate to identify correlation between CRF and quality of life using Pearson product moment correlation and Spearman test. Both were numeric variables with Î± < 0.05 and CI 95%. Result: The result of the study showed there was correlation between CRF and Global Health Status/ Quality of Life with p = 0.045 and r = -0.369 and level of correlation was weak. CRF was also correlated with Physical Functioning whereby p = 0.001 and r = -0.624 and level of correlation was strong. There was no correlation between CRF and other scales. Conclusion: There was correlation between CRF and Global Health Status/ Quality of Life and Physical Functioning and there was no correlation with other scales.